(untitled) (Herald of Journalism, 2020)
The article is devoted to the theoretical system of publicity functions. On the basis of study of the classification of famous the author pulled out six basic functions of modern publicity’s: 1) contacts; 2) cognitive; 3) demonstration; 4) expressive; 5) axiological 6) organizing-mobilization. In article reasons of each function are given in the article.